COMPARATIVE ANALYSIS OF ENERGY EFFICIENCY AND ECONOMIC SUSTAINABILITY IN PUBLIC BUILDINGS: A CASE STUDY OF A KINDERGARTEN USING HEAT PUMPS AND PHOTOVOLTAIC SYSTEMS (Natural Resources and Technology, 2025)
Energy efficiency improvements and renewable energy integration in public buildings represent a significant step toward reducing operational costs and minimizing environmental impact. This study presents a comprehensive analysis of the energy performance of a kindergarten in Macedonia, with a total area of 1 200 m², an annual electricity consumption of 25 000 kWh, and a yearly consumption of 16 700 liters of extra light fuel oil for heating. The objective is to identify the most efficient and cost-effective solution by comparing three scenarios. The first scenario considers the current situation, where electricity is procured from the Universal Supplier, and heating relies on extra light fuel oil. An alternative option is analyzed, considering electricity procurement on the free market. The second scenario involves heating with a 150 kW heat pump powered by electricity procured from the free market and the Universal Supplier. The third scenario includes the installation of a 40 kWp photovoltaic (PV) system on the kindergarten's roof, utilizing the generated electricity for self-consumption, selling surplus electricity, heating with a 150 kW heat pump, and procuring additional electricity as needed. The study evaluates the return on investment (ROI) and operational cost savings for each scenario, with and without accounting for the reduction in CO₂ emissions based on the European carbon pricing mechanism. The results demonstrate the economic feasibility and environmental benefits of transitioning to renewable energy and energy-efficient heating systems in public institutions.
Keywords: energy consumption, carbon emissions, return on investment, operational costs, renewable energy integration, techno-economic analysis.